10x-14+13=6x+26+x

Simple and best practice solution for 10x-14+13=6x+26+x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 10x-14+13=6x+26+x equation:


Simplifying
10x + -14 + 13 = 6x + 26 + x

Reorder the terms:
-14 + 13 + 10x = 6x + 26 + x

Combine like terms: -14 + 13 = -1
-1 + 10x = 6x + 26 + x

Reorder the terms:
-1 + 10x = 26 + 6x + x

Combine like terms: 6x + x = 7x
-1 + 10x = 26 + 7x

Solving
-1 + 10x = 26 + 7x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-7x' to each side of the equation.
-1 + 10x + -7x = 26 + 7x + -7x

Combine like terms: 10x + -7x = 3x
-1 + 3x = 26 + 7x + -7x

Combine like terms: 7x + -7x = 0
-1 + 3x = 26 + 0
-1 + 3x = 26

Add '1' to each side of the equation.
-1 + 1 + 3x = 26 + 1

Combine like terms: -1 + 1 = 0
0 + 3x = 26 + 1
3x = 26 + 1

Combine like terms: 26 + 1 = 27
3x = 27

Divide each side by '3'.
x = 9

Simplifying
x = 9

See similar equations:

| 5j=-84.05 | | 6x-3-11-8x=2 | | 2b+6=4b+2 | | 9x-8-x=-3x+80 | | 4y=2*(y-5)-2 | | -5+15y=20 | | -x=3x-3 | | 3/10n=12 | | 12(x-1)=4x+44 | | 3v^2-27v+54=0 | | 3z-24(1-z)=5(1-2z)-12 | | (4x-1)+(4x-1)+(3x+2)+(3x+2)+(3x+2)=157 | | 1/3m=2/5 | | x^4-x^2=11x^2+64 | | 2x+6y=130 | | |(1/3)x-4|=2 | | 3v^2-27v+55=0 | | 4(x-2)=-1(x+3) | | 14x+4=157 | | 230-40Q=P | | 440=3w-6 | | 2n-5=4n-8-n | | 5-(4x-5)=32 | | 4(r-12)=6 | | (x-5)(x+1)=16 | | -9x+7=-6x-11 | | 0.5=-16x^2+4.5 | | -91=6(v-7)-1 | | 2x^2+4x=-12 | | (x-5)(x+1)=161 | | 76+2x+(5x-2)=180 | | f(x)=4*2 |

Equations solver categories